Newly Arrived Migrant Students’ perceptions of second language learning conditions in Emergency Remote Teaching: the case of Flanders - Seynhaeve, Shauny (Dutch Journal of Applied Linguistics, 2025)
When Newly Arrived Migrant Students (NAMS) enter their country of arrival, they are expected to get familiarized with the new educational system, while simultaneously acquiring the language of instruction. Within this context, comprehensible input and meaningful interaction are needed to effectively acquire a second language. While educational systems worldwide switched to Emergency Remote Teaching due to the outbreak of COVID-19 in 2020, such online learning environments often fail to meet these language learning conditions adequately. We investigated NAMS’ perceptions of second language learning conditions during online learning through six semi-structured focus groups with 23 NAMS. Results show that participants encountered greater difficulties in understanding their teachers’ input in online classes. Although alternative input channels, such as video recordings, reportedly did not entirely compensate the lack of interaction in the online environment, participants believed that processing alternative sources of input enabled them to maintain their Dutch proficiency through Emergency Remote Teaching.